Design, Formulation and Characterization of Solid-lipid Nanoparticles for Anti-retroviral Drug (Asian Journal of Pharmaceutics (AJP), 2025)
Treating human immunodeficiency virus (HIV)/acquired immunodeficiency syndrome effectivelyremains a significant challenge due to issues, such as low absorption, frequent dosing, and side effects associatedwith traditional antiretroviral drugs. This study focuses at solid lipid nanoparticles (SLNs) as a new way to deliverdrugs. These nanoparticles could provide better control over how these drugs are absorbed and released in the body,making treatment more manageable for patients. Materials and Methods: We made SLNs utilizing ultrasonicationand high-shear homogenization. A commonly used antiretroviral drug was embedded in a lipid matrix made fromglyceryl monostearate and stabilized with Poloxamer 188. Researchers carefully evaluated these nanoparticlesfor key properties, such as the size of the particles, the size distribution polydispersity index (PDI), and thesurface charge (zeta potential), drug retention (entrapment efficiency), and the timing of drug release in lab tests.Results: The resulting SLNs had an average particle size of